2015
DOI: 10.30935/cedtech/6140
|View full text |Cite
|
Sign up to set email alerts
|

Examining Digital Literacy Competences and Learning Habits of Open and Distance Learners

Abstract: The purpose of the study is to examine digital literacy competences and learning habits of learners enrolled in the open and distance education system of Anadolu University in Turkey. Data were gathered from 20.172 open and distance learners through a survey which included four parts: demographic information, abilities to use digital technologies, learning habits, preferences in using digital technologies for learning purposes. Principal Component Factor Analysis was applied in order to group and classify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 9 publications
1
46
1
12
Order By: Relevance
“…Digital literacy encourages curiosity and allows individuals to evaluate information in a critical way. By increasing the ability to use digital resources, digital literacy helps individuals feel themselves relatively safe in using technology (Özdamar Keskin et al, 2015). However, currently there are still many people who need training so that they can use and manage information networks with the help of technology (Hague & Payton, 2010).…”
Section: Competence Of Attitudes Using Digital Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital literacy encourages curiosity and allows individuals to evaluate information in a critical way. By increasing the ability to use digital resources, digital literacy helps individuals feel themselves relatively safe in using technology (Özdamar Keskin et al, 2015). However, currently there are still many people who need training so that they can use and manage information networks with the help of technology (Hague & Payton, 2010).…”
Section: Competence Of Attitudes Using Digital Devicesmentioning
confidence: 99%
“…With the advent of mobility, digital tools have become an integral part of human life and it also enhances three important factors such as speed, virtuality, and networks (Özdamar Keskin, Özata, Banar, & Royle, 2015). These digital products are believed to make a positive contribution to the practice of better teaching and learning (Robertson, Fluck, Webb, & Loechel, 2004;Wang, 2008)).…”
Section: Introductionmentioning
confidence: 99%
“…La alfabetización digital es una categoría conceptual necesaria en el desarrollo de los procesos educativos mediados por el uso de las TIC ya sea en ambientes mixtos o virtuales y en todos los niveles de escolaridad. Más allá del dominio funcional de estas tecnologías, interesa que estudiantes y maestros se aproximen al uso de estas, como co-partícipes de la cultura digital y productores activos de conocimiento a través de ellas, condición propia del mundo actual (Ozdamar-Keskin et al, 2015). El 35% de los artículos analizados indagan acerca de experiencias de alfabetización, articuladas con los beneficios y ventajas del B-Learning (B-L).…”
Section: Figuraunclassified
“…The important thing is how the new literacy can be consumed based on the need. Furthermore, [11] conducted a survey research on digital literacy competences and learning habit of to 20.172 open and distance learners and the result revealed that most of the participants were in basic competences level.…”
Section: Introdutionmentioning
confidence: 99%
“…The survey focused on the digital habits of learners was conducted by previous works such as [14] : [4]: [3]: [6], [7] : [11] . Moreover, [10] did a study in order to explore the development of Australian Aboriginal Pre-service teachers' digital literacy and understanding of digital pedagogies for teaching literacy.…”
Section: Introdutionmentioning
confidence: 99%